A percepção de adultos jovens sobre a perda de um irmão na infância: um estudo exploratório - Pessoa, Gabriella Costa (2017)
Among all happenings capable of altering one’s family dynamics, the death is one to require adaptive answers, especially in regard of the ensuing grief. Bereavement occurs whenever there was a bond with the deceased person. Its process entails a variety of subjective aspects, unique to each loss. For children, the understanding of death differs from the adult experience, according to the child’s developmental stage. A loss occurred during childhood will likely be revisited and resignified throughout a lifetime, regarded that the bond between siblings bears potential for intense and diverse life experiences. When one loses a sibling, also loses the possibility of a future shared with someone from the same generation, who partakes the same family origins. In addition, a child who loses a sibling has grieving parents that may not be able to provide the needed atmosphere for a healthy development. The exploratory research focuses on long-term sibling bereavement, aiming to understand better how the loss of a sibling during childhood reflects into adulthood. We used the qualitative method with discourse analysis applied to a single meeting interview with two young adults of 18-35 years old who lost a 0-12-years-old brother or sister during childhood. The grief process was understood from the categories: understanding of death in childhood; participation in related events; grief reactions; find refuge; parental grief; communication; support; disenfranchised grief; having another child; Recurrence; fantasy; curiosity; ambiguity; presumed world; religion; personal growth; continuing bond; therapy. The results indicate that the loss of a brother or sister during childhood can produce changes in different aspects of the emotional development of the life of the bereaved and that talking about it is beneficial